Kronenberg: Williams Textbook of Endocrinology - Henry M. Kronenberg, MD, Shlomo Melmed, MD, FRCP (elsevier, 2008)
Welcome to the eleventh edition of Willams Textbook of Endocrinology. Although Robert Williams inaugurated this book more than 50 years ago, the goals of the text have not changed. Williams stated his goal as â€œa condensed and authoritative discussion of the management of clinical endocrinopathies based upon the application of fundamental information obtained from chemical and physiological investigation.â€ Of course, today we would add â€œgenetic and epidemiologic investigation, as well as the wealth of clinical trial dataâ€ as sources of information that aids clinical management. The immense and ongoing new information from multiple disciplines, in fact, makes a synthetic exercise like this textbook more relevant than ever to help guide endocrinologists in the care of their patients. To encourage the goal of synthesis, we continue to ask a small number of distinguished authors to work together to present entire areas of endocrine science. The mandate for concise presentations acknowledges both the time pressures on today's physicians and the desire to make the text affordable and easily navigated.